URGENCY OF MORAL IN THE WORLD OF AL-QUR'AN PERSPECTIVE - Ali Nurdin (STIT AL-AMIN KREO TANGERANG, 2020)
This paper discusses the perspective of the Koran on the urgency of morals in the business world. This paper focuses its study on descriptions of the morals that employers and employees must possess in running a business field in order to comply with the corridors stipulated by the al-Qur'an. The data sources in this article were obtained from scientific works that discuss morals in the perspective of the Qur'an. This main source is strengthened and supported by other relevant data (called secondary data), namely in the form of books or sources from other writers who talk about morals in the perspective of the Koran. This paper is a research library (library research) using a qualitative approach, which tries to describe a variable, symptom or situation as it is and is not intended to test certain hypotheses. The results of this paper show that among the main factors in supporting success as both an entrepreneur and a worker is having good ethics and anyone who carries out his business activities that does not heed ethics is sure to experience destruction one day.